Peripheral Gangerene, an Unusual Presentation of Infantile Kawasaki: A Case Report and Literature Review - Tahghighi, Fatemeh; Bakhtiari Koohsorkhi, Maryam; Ziaee, Vahid (Case Reports in Rheumatology, 2021)
Introduction. Diagnosing infantile Kawasaki disease with atypical symptoms is difficult, and it also has higher risk of coronary abnormalities which is one of the most common complications of KD. Other complications such as pericardial effusion, mitral insufficiency, congestive heart failure, myocardial systolic dysfunction, and systemic vasculitis were also reported. Peripheral gangrene and necrosis are among the rare complications of this systemic vasculitis. Case Presentation. We report an 8-month-old girl with prolonged fever, generalized petechial rash, cracked erythematous lips, edema, and coronary ectasia who received two doses of IVIG in another center, but short after her discharge, she started to develop a necrotic plaque on her knee. She was admitted in our hospital, and the repeat echocardiography showed sustained coronary ectasia. She received 3 doses of methylprednisolone pulse therapy and was discharged with aspirin and prednisolone. In the follow-up visits, the coronary ectasia was resolved and the necrotic ulcer was healing with a scar. Conclusions. The diagnosis of Kawasaki disease and echocardiographic evaluation of the coronary arteries should be considered in young infants with prolonged fever of unknown origin. Peripheral gangrene is a rare but important complication of infantile Kawasaki disease, although the exact mechanism in not fully understood.